Population pharmacokinetics of factor IX in hemophilia B patients undergoing surgery. (28th October 2018) - Preijers, T.; Hazendonk, H. C. A. M.; Liesner, R.; Chowdary, P.; Driessens, M. H. E.; Hart, D.; Keeling, D.; Laros‐van Gorkom, B. A. P.; van der Meer, F. J. M.; Meijer, K.; Fijnvandraat, K.; Leebeek, F. W. G.; et al.
Abstract : Essentials Factor IX (FIX) dosing using body weight frequently results in under and overdosing during surgery. We aimed to establish a population pharmacokinetic (PK) model describing the perioperative FIX levels. Population PK parameter values for clearance and V1 were 284 mL h −1 70 kg −1 and 5450 mL70 kg −1 . Perioperative PK parameters differ from those during non‐surgical prophylactic treatment. Summary: Background: Hemophilia B is a bleeding disorder characterized by a deficiency of coagulation factor IX (FIX). In the perioperative setting, patients receive FIX concentrates to ensure hemostasis. Although FIX is usually dosed according to bodyweight, under‐ and overdosing occurs frequently during surgery. Aim: The objective was to quantify and explain the interpatient variability of perioperatively administered plasma‐derived (pd) and recombinant (r) FIX concentrates. Methods: Data were collected from 118 patients (median age, 40 years [range, 0.2–90]; weight, 79 kg [range, 5.3–132]) with moderate (28%) or severe hemophilia B (72%), undergoing 255 surgical procedures. Population pharmacokinetic (PK) parameters were estimated using nonlinear mixed‐effect modeling in NONMEM. Results: Measured perioperative FIX level vs. time profiles were adequately described using a three‐compartment PK model. For a typical 34‐year‐old patient receiving rFIX, clearance (CL), intercompartmental clearance (Q2, Q3), distribution volume of the central compartment ( V 1) and peripheral compartments ( V 2, V 3) plus interpatient variability (%CV) were: CL, 284 mL h −1 70 kg −1 (18%); V 1, 5450 mL70 kg −1 (19%); Q2, 110 mL h −1 70 kg −1 ; V 2, 4800 mL70 kg −1 ; Q3, 1610 mL h −1 70 kg −1 ; V 3, 2040 mL70 kg −1 . From 0.2 years, CL and V 1 decreased 0.89% and 1.15% per year, respectively, until the age of 34 years. Patients receiving pdFIX exhibited a lower CL (11%) and V 1 (17%) than patients receiving rFIX. Interpatient variability was successfully quantified and explained. Conclusions: The estimated perioperative PK parameters of both pdFIX and rFIX are different from those reported for prophylactic treatment. The developed model may be used to apply PK‐guided dosing of FIX concentrates during surgery.